SPG302 Reverses Synaptic and Cognitive Deficits Without Altering Amyloid or Tau Pathology in a Transgenic Model of Alzheimer's Disease - Trujillo-Estrada, Laura Isabel; Vanderklish, Peter; Minh Thu Nguyen, Marie; Kuang, Run Rong; Nguyen, Caroline; Huynh, Eric; da Cunha, Celia; Ibarra Javonillo, Dominic; Forner, Stefania; Martini, Alessandra C.; Sarraf, Stella; Simmon, Vicent; et al. (Elsevier, 2021)
Alzheimer’s disease (AD) is conceptualized as a synaptic failure disorder in which loss of glutamatergic synapses is a major driver of cognitive decline. Thus, novel therapeutic strategies aimed at regenerating synapses may represent a promising approach to mitigate cognitive defcits in AD patients. At present, no disease-modifying drugs exist for AD, and approved therapies are palliative at best, lacking in the ability to reverse the synaptic failure. Here, we tested the efcacy of a novel synaptogenic small molecule, SPG302 — a 3rd-generation benzothiazole derivative that increases the density of axospinous glutamatergic synapses — in 3xTg-AD mice. Daily dosing of 3xTg-AD mice with SPG302 at 3 and 30 mg/kg (i.p.) for 4 weeks restored hippocampal synaptic density and improved cognitive function in hippocampal-dependent tasks. Mushroom and stubby spine profles were increased by SPG302, and associated with enhanced expression of key postsynaptic proteins — including postsynaptic density protein 95 (PSD95), drebrin, and amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) — and increased colocalization of PSD95 with synaptophysin. Notably, SPG302 proved efcacious in this model without modifying Aβ and tau pathology. Thus, our study provides preclinical support for the idea that compounds capable of restoring synaptic density ofer a viable strategy to reverse cognitive decline in AD.
Keywords: Alzheimer, Enfermedad de; Alzheimer's disease; Dendritic spines; Synaptic deficits; 3xTg-AD mice; SPG302; Synaptic markers